ANALISIS FAKTOR-FAKTOR BERPENGARUH TERHADAP PRODUKTIVITAS KERJA BENDAHARAWAN SATUAN (BENSAT) POLDA SULAWESI SELATAN - Muh Asdar (AkMen JURNAL ILMIAH, 2018)
The purpose of this research is 1) To know and analyze the level of Work Productivity of Treasurer of South Sulawesi Police Unit, 2) To know and analyze what factors influence the productivity of the Treasurer in South Sulawesi Police Work Unit, and 3) To know and analyze the most factors dominant influence on work productivity at the Treasurer of South Sulawesi Police Unit. The method of analysis used in this research is Multiple Regression analysis method. The research data was obtained from the staff of Bendaharawan Satuan (BENSAT) of South Sulawesi Police. The results of this study indicate that: 1) The promotion of job title, salary, work facilities and education and training have a significant effect on the work productivity of Civil Service Police in South Sulawesi Police Headquarters, 2) To improve work productivity of employees must also pay attention to work design to encourage specialization work so that the development of employee's ability to knowledge, skills, work ability is more optimal, and thus will encourage the achievement of organizational goals by paying attention to the concept of goal alignment, 3) The most dominant reward factor because there is a desire to obtain promotion, periodic salary increase, other reward signs in the form of achievement symbols, and 4) The salary factor is insignificant, because the salary for the treasurer is a provision that can not be changed either the treasurer is productive or not salary is still running unless it is PTD Hello